Sex-selective abortions over the past four decades in China - Li Mei; Quanbao Jiang (Population Health Metrics, 2025)
Abstract Background China now faces multiple challenging demographic and public policy problems that have emerged from four decades of sex-selective induced abortions. The sex-selective induced abortion of female fetuses has been under-examined quantitatively in China. Methods Using annual data on the officially registered number of births, induced abortions, and SRB data, we estimate the annual number of sex-selective abortions and then estimated two related proportions over the past decades. Results The annual proportions and number of selective abortions rose in the 1980s with the strict family planning policy and the diffusion of sex identification technology, remained at a high level between 1990 and 2010, and then declined, totaling 30.04 million. The abortion of second-order female fetuses was the largest proportion of all sex-selective abortions but declined after 2000 partly due to the change in birth composition by order. Children's composition affected sex-selective practice. Village selective abortions accounted for the majority of all selective abortions but decreased markedly in 2010 with changes in birth composition by residence. The rural–urban comparison by order indicated that urban couples were not less likely to abort female fetuses than their rural counterparts. Sex-selective abortions still exhibit provincial differences. Conclusions In China, the long-standing preference for sons, easy access to sex-selective technologies, and the spontaneous fertility decline have led to the continued practice of selectively aborting female fetuses, despite its prohibition. As a result, the imbalanced sex ratio may take years to normalize.